Microwave decontamination of eyelid warming devices for the treatment of meibomian gland dysfunction. Issue 4 (August 2016) - Bilkhu, Paramdeep; Wolffsohn, James S.; Hilton, Anthony; Matthews, Gabrielle; Legood, Simon; Riley, Liam
Highlights: Warm compresses effectively manage MGD, but there may be a contamination risk. Cotton flannels & eyebags inoculated & tested; no, therapeutic or sanitisation heat. Therapeutic or sanitation heating reduced bacteria on eyebags. Sanitisation heating required to reduce bacteria for flannels. However, patients advised to heat to sanitisation temperatures on initial use. Abstract: Purpose: The role of bacteria in meibomian gland dysfunction is unclear, yet contamination of compresses used as treatment may exacerbate this condition. This study therefore determined the effect of heating on bacteria on two forms of compress. Methods: Cotton flannels and MGDRx EyeBags (eyebags) were inoculated by adding experimental inoculum ( Staphylococcus aureus, Streptococcus pyogenes, Pseudomonas aeruginosa ; one species for each set of 3 eyebags and flannels). One of each were then randomised in to 3 groups: no heating (control); therapeutic (47.4 ± 0.7 °C); or sanitisation (68 ± 1.1 °C). After treatment, bacteria cell numbers were calculated. The experiment was repeated in triplicate. Results: There was a statistically significant difference between each treatment with the eyebag for S. aureus (control = 7.15 ± 0.11 log C /ml, therapeutic heating = 5.24 ± 0.59 log C /ml, sanitisation heating = 3.48 ± 1.43 log C /ml; P < 0.001) and S. pyogenes (7.36 ± 0.13, 5.73 ± 0.26, 4.75 ± 0.54; P < 0.001). P. aeruginosa also showed a significant reduction ( P < 0.001) from control (6.39 ± 0.34) to therapeutic (0.33 ± 0.26) and sanitisation (0.33 ± 0.21), but the latter were similar ( P = 1.000). For the flannels, there was significant difference between each treatment for S. aureus (6.89 ± 0.46, 3.96 ± 1.76, 0.42 ± 0.90; P < 0.001). For S. pyogenes, there was a significant reduction ( P < 0.001) from control (7.51 ± 0.10) to therapeutic (5.91 ± 0.62) and sanitisation (5.18 ± 0.8), but the latter were similar ( P = 0.07). For P. aeruginosa, there was a significant difference ( P < 0.001) from control (7.15 ± 0.36) to sanitisation (5.83 ± 0.44); but not to therapeutic (6.84 ± 0.31) temperatures ( P = 0.07). Conclusions: Therapeutic heating produces a significant reduction in bacteria on the eyebags, but only sanitisation heating appears effective for flannels. However, patients should be advised to heat the eyebag to sanitisation temperatures on initial use.